Aseptic Abscesses and Inflammatory Bowel Disease: Two Cases and Review of Literature. (6th February 2017) - Bollegala, Natasha; Khan, Rishad; Scaffidi, Michael A.; Al-Mazroui, Ahmed; Tessolini, Jenna; Showler, Adrienne; Colak, Errol; Grover, Samir C.
Abstract : Background . Aseptic abscesses (AA) are sterile lesions that represent an extraintestinal manifestation (EIM) of inflammatory bowel disease (IBD). Though Canada has the highest prevalence of IBD in the world, reports of IBD-associated AA are absent in Canada. This may represent a different IBD phenotype or underrecognition and underreporting. Purpose . To explore AA as a possible EIM of IBD and evaluate clinical and investigative findings among patients with IBD-associated AA. Methods . Retrospective chart and literature reviews were performed to find cases of IBD-associated AA at our institution and in the literature. Results . We identified 2 cases of IBD-associated AA in our institution. Both patients had ulcerative colitis and presented with fever, abdominal pain, and weight loss. Radiological workup and aspiration showed sterile splenic abscesses. The AA were unresponsive to antibiotics. One patient improved on corticosteroids and one underwent splenectomy. We retrieved 37 cases of IBD-associated AA from the literature. All patients showed no evidence of infection, failed to resolve with antibiotics, and, if attempted, improved on corticosteroids. Conclusions . Our cases are the first reported in Canada. They support literature which suggests AA as an EIM of IBD and may help increase recognition and reporting of this phenomenon.